2016
DOI: 10.1161/circimaging.115.004077
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Magnetic Resonance Myocardial Feature Tracking

Abstract: Abstract-Heart failure-induced cardiovascular morbidity and mortality constitute a major health problem worldwide and result from diverse pathogeneses, including coronary artery disease, nonischemic cardiomyopathies, and arrhythmias. Assessment of cardiovascular performance is important for early diagnosis and accurate management of patients at risk of heart failure. During the past decade, cardiovascular magnetic resonance myocardial feature tracking has emerged as a useful tool for the quantitative evaluatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
206
0
11

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 313 publications
(233 citation statements)
references
References 64 publications
4
206
0
11
Order By: Relevance
“…Buss et al 28 prospectively studied 210 patients who had DCM with standard CMR including measurement of LGE during the median follow-up period of 5.3 years, and demonstrated that LV feature tracking longitudinal strain assessed with CMR is an independent predictor of survival in patients with DCM. These strongly support our results, although feature tracking longitudinal strain based on CMR have some problems to overcome regarding the agreement with longitudinal strain based on tagging CMR, interobserver reproducibility and temporal resolution 29 30…”
Section: Discussionsupporting
confidence: 85%
“…Buss et al 28 prospectively studied 210 patients who had DCM with standard CMR including measurement of LGE during the median follow-up period of 5.3 years, and demonstrated that LV feature tracking longitudinal strain assessed with CMR is an independent predictor of survival in patients with DCM. These strongly support our results, although feature tracking longitudinal strain based on CMR have some problems to overcome regarding the agreement with longitudinal strain based on tagging CMR, interobserver reproducibility and temporal resolution 29 30…”
Section: Discussionsupporting
confidence: 85%
“…Clinical potential of CMR-FT has been recently described [18, 19]. However, it must be borne in mind that different methods have different strengths and limitations as they rely on different strategies for optimal tracking results: some use pure two-dimensional search windows of different sizes; others also include tracking by local M-mode representation along various directions that can be more efficient and accurate when motion is predominantly along one direction (like the longitudinal displacement of atrio-ventricular junctions).…”
Section: Technology Of Tissue Trackingmentioning
confidence: 99%
“…Our study, therefore, sought to give insight into the pathophysiological role of LA function as measured by CMR-FT, given the advantages in myocardial border delineation and spatial resolution, 13,23 in relation to exercise capacity, invasively determined diastolic LV function and CMR-derived LV volume-time curves.…”
Section: Von Roeder Et Al Influence Of Atrial Function In Hfpefmentioning
confidence: 99%
“…Cardiac magnetic resonance feature tracking (CMR-FT) is a novel tool to assess myocardial deformation directly from standard steady-state-free precession cine CMR images. 13 This allows for quantifying myocardial deformation without the need for complex tagging sequences. …”
mentioning
confidence: 99%